In vitro Sterilization, Rooting and Acclimatization of Difficult-to-root Bougainvillea Cultivars - Kumari, Pratiksha; Swaroop, Kishan; Janakiram, T.; Singh, S. K.; Prasad, K. V.; Jain, Ritu (International Journal of Bio-resource and Stress Management, 2023)
Bougainvillea is a widely used high value landscape plant. It is commonly propagated by hardwood cuttings but this method is tedious and time consuming. Moreover, there are certain cultivars where rooting is very low. For easy, quick, and mass multiplication of such cultivars, tissue culture technique can be put to use. Tissue culture has been proved to be useful for successful multiplication in case of a number of vegetatively propagated shrubs. Present investigation was carried out in order to standardize a protocol for in vitro rooting and acclimatization of two difficult-to-root Bougainvillea cultivars, viz., Mahatma Gandhi and Refulgens. Nodal sections with axillary buds were excised, surface-sterilized and cultured on MS medium supplemented with plant growth regulators. Agitation of explants in carbendazim (0.1%)+Metalaxyl (0.1%)+8-HQC (200 mg l-1) for 3 hr followed by quick dip in ethyl alcohol (70%; v/v) for 30 sec and surface sterilization in HgCl2 (0.1%) for 5 min was found to be best for eliminating microbial contamination prior to inoculation. In vitro grown micro-shoots were grown in MS media along with various concentrations of NAA and/or IBA in order to induce rooting. Highest in vitro rooting (64.99%) of micro-shoots was noted in the treatment where half-strength MS medium was supplemented with 1.0 mg l-1 IBA. Acclimatization was most effective in glass jar with polypropylene cap. The hardened plant lets were successfully transferred to the glasshouse after a short period of in vitro acclimatization.